(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
Information technologies are among the most relevant areas of activity, as the use of innovative products is expanding and requires modernization. To create or update a project in a timely manner, you need to connect IT specialists with the appropriate characteristics. This article describes the key requirements for an IT specialist job.